The Right to Be Forgotten in the Digital Age: The Challenges of Data Protection Beyond Borders. (March 2020) - Fabbrini, Federico; Celeste, Edoardo
Abstract: This article explores the challenges of the extraterritorial application of the right to be forgotten and, more broadly, of EU data protection law in light of the recent case law of the ECJ. The paper explains that there are good arguments for the EU to apply its high data protection standards outside its borders, but that such an extraterritorial application faces challenges, as it may clash with duties of international comity, legal diversity, or contrasting rulings delivered by courts in other jurisdictions. As the article points out from a comparative perspective, the protection of privacy in the digital age increasingly exposes a tension between efforts by legal systems to impose their high standards of data protection outside their borders – a dynamic which could be regarded as 'imperialist' – and claims by other legal systems to assert their own power over data – a dynamic which one could name 'sovereigntist'. As the article suggests, navigating between the Scylla of imperialism and the Charybdis of sovereigntism will not be an easy task. In this context, greater convergence in the data protection framework of liberal democratic systems worldwide appears as the preferable path to secure privacy in the digital age.